2007
DOI: 10.1037/0021-9010.92.4.1159
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision and workplace deviance and the moderating effects of negative reciprocity beliefs.

Abstract: In this study, the authors examine the relationship between abusive supervision and employee workplace deviance. The authors conceptualize abusive supervision as a type of aggression. They use work on retaliation and direct and displaced aggression as a foundation for examining employees' reactions to abusive supervision. The authors predict abusive supervision will be related to supervisor-directed deviance, organizational deviance, and interpersonal deviance. Additionally, the authors examine the moderating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
1,238
6
30

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,206 publications
(1,323 citation statements)
references
References 72 publications
49
1,238
6
30
Order By: Relevance
“…Regression results revealed that workplace bullying was significantly related to employees' unethical behavior in the workplace. This result corroborates findings of Mitchell and Ambrose (2007) who found a significant positive relationship between abusive supervision and workplace deviance.…”
Section: Discussion and Recommendationssupporting
confidence: 82%
“…Regression results revealed that workplace bullying was significantly related to employees' unethical behavior in the workplace. This result corroborates findings of Mitchell and Ambrose (2007) who found a significant positive relationship between abusive supervision and workplace deviance.…”
Section: Discussion and Recommendationssupporting
confidence: 82%
“…Ashforth, 1994Ashforth, , 1997Duffy et al, 2002;Frone, 2000;Grandey et al, 2007;Mitchell and Ambrose, 2007;Tepper, 2000Tepper, , 2007Yagil, 2006). The emotional outcomes revealed here begin to address Brief and Weiss' (2002) call for additional empirical research on leaders' affect on followers' moods and emotions.…”
Section: A Unique Contributionmentioning
confidence: 99%
“…"My nearest superior puts me down in front of others"). The scale was originally developed by Tepper (2000) and the subscales reflecting active-aggressive and passive-aggressive forms of abusive supervision were discerned by Mitchell and Ambrose (2007).…”
Section: Methodsmentioning
confidence: 99%